2011
DOI: 10.1152/ajpheart.00967.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbenoxolone on flow-mediated vasodilatation in healthy adults

Abstract: Gap junctions play a key role in maintaining the functional integrity of the vascular wall. Using carbenoxolone (CBX) as a gap junction blocker, we aimed to assess the contribution of gap junctions in the vascular wall to flow-mediated vasodilatation (FMD) in healthy adults. Percentage FMD (%FMD) and circulating vasoactive molecules/activity, including atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), aldosterone, cortisol, plasma renin activity (PRA), and endothelin (ET-1) , were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…), which was used to block the gap junctions of blood vessels. The dose and route of CBX administration was determined based on previous studies (Leshchenko et al, 2006; Lan et al, 2011). One study showed that CBX was not detected in the cerebrospinal fluid following systemic administration at a similar dose (50 mg/kg; i.p.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), which was used to block the gap junctions of blood vessels. The dose and route of CBX administration was determined based on previous studies (Leshchenko et al, 2006; Lan et al, 2011). One study showed that CBX was not detected in the cerebrospinal fluid following systemic administration at a similar dose (50 mg/kg; i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results may suggest that administered CBX did not act on the brain parenchyma, but possibly on the cerebral vasculature. It has been reported that vasodilation induced by ischemia-reperfusion (due to nitric oxide generated from vascular endothelial cells) in the brachial artery is attenuated by systemic administration of CBX (Lan et al, 2011), indicating that systemically administered CBX acts on the vascular endothelium. Therefore, the present study results may support the hypothesis that pial arterial dilation associated with neuronal activity propagates through gap junctions of the cerebral vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the corresponding channels have been investigated as potential targets to affect EDH [147,149]. Endothelial hyperpolarization can spread via myoendothelial gap junctions to directly induce VSMC hyperpolarization: the role of gap junctions has been implicated also in humans in vitro and in vivo as carbenoxolone, a nonspecific gap junction blocker, diminished conducted vasodilation in isolated human coronary arterioles [150], and, moreover, reduced FMD in the brachial artery of healthy volunteers [151]. The term conducted dilation has been used to denote electrotonic transmission of local hyperpolarization, and may spread several mm upstream independent of alterations in shear stress [116,119,152].…”
Section: Endothelium-dependent Relaxations Beyond No: Hyperpolarizationmentioning
confidence: 99%
“…Estes autores mostraram que o desacoplamento promovido pelo ácido glicirretínico 18-beta correlacionou-se com redução da forma fosforilada P2 da Cx43 e aumento da forma não fosforilada da proteína (já é conhecido que o estado de fosforilação da Cx43 pode alterar a condutância do canal, sendo que as formas fosforiladas normalmente estão relacionadas com aumento da probabilidade do canal se encontrar no estado aberto - Godwin et al, 1993;Oelze et al, 1995;Cotrina et al, 1998). No entanto, além da Cx43, a CBX também inibe canais de JC compostos por outras Cx (Lan et al, 2011).…”
Section: Análise Da Expressão De Cx36unclassified